Electronic and charge transfer properties of bio-inspired flavylium ions for applications in TiO2-based dye-sensitized solar cells. Issue 9 (21st July 2017) - Calogero, Giuseppe; Citro, Ilaria; Di Marco, Gaetano; Caramori, Stefano; Casarin, Laura; Bignozzi, Carlo Alberto; Avó, João; Jorge Parola, A.; Pina, Fernando
Abstract : We present a complete study on four synthetic environmentally friendly flavylium salts employed as sensitizers for dye-sensitized solar cells (DSSCs). Abstract : We present here a complete study on four synthetic environmentally friendly flavylium salts employed as sensitizers for dye-sensitized solar cells (DSSCs). The effect of several donor groups on the molecular structure of flavylium ions was investigated by combining electrochemical, spectroscopic and computational means. The computational investigation indicated that these molecules can interact strongly with the TiO2 surface by a single OH group of the dihydroxybenzene moiety, and can efficiently inject electrons into the TiO2 following the excitation of their lowest singlet states exhibiting charge transfer (CT) character. In general, all dyes within the explored series exhibited quite good regeneration efficiencies, often ≥70%, in the presence of an iodide electron donor, explaining the high IPCEs and photocurrents recorded in the presence of high lithium content electrolytes. The combination of molecular orbital calculations and electrochemical measurements has also revealed that the introduction of donor groups on the benzopyrylium ring has a generally positive effect resulting in an extended low energy light harvesting and in a potential improvement of the photoinduced charge separation at the semiconductor/dye/electrolyte interface. It also increases the reversibility of the oxidative redox processes of these bio-inspired species, a feature in favour of their long-term stability. At present the best dye within the explored series is 7-( N, N -diethylamino)-3′, 4′-dihydroxyflavylium chloride based on a dialkylamine donor which is capable of delivering, under optimized conditions, a short-circuit current density of 15 mA cm −2 . This is the highest value so far obtained for synthetic analogues of anthocyanins.